Molecular Imaging Studies on CD133+ Hematopoietic Stem Cells From Human Umbilical Cord Blood - Pavon, L.F.; Marti, L.C.; Sibov, T.T.; Camargo-Mathias, M.I.; Amaro, Jr.E.; Gamarra, L.F. (IntechOpen, 2012)
None